AKTIVISME YUDISIAL DALAM PENAFSIRAN BAHASA KONSTITUSI: ANALISIS TEORETIS DAN STUDI KASUS PUTUSAN MAHKAMAH KONSTITUSI INDONESIA - Sulistyowati; Ardi Christesar Sihombing; Gusti Bintang Maharaja (JURNAL SKRIPTA, 2026)
The Constitutional Court of the Republic of Indonesia is vested with an absolute mandate as the final interpreter of the constitution, whose decisions are final and binding erga omnes. In exercising this authority, the Court faces a doctrinal dilemma between judicial activism—which fosters progressive interpretation to realize substantive justice—and judicial restraint, which emphasizes adherence to the literal text and respect for the separation of powers. This article aims to analyze the theoretical foundation of constitutional textual interpretation and to identify the forms and implications of judicial activism within the judgments of the Indonesian Constitutional Court. The research methodology employed is a literature review with a normative qualitative approach, utilizing primary and secondary legal materials analyzed through descriptive-analytical methods. The research findings indicate that the Indonesian Constitutional Court has undergone a dynamic paradigm shift from judicial restraint toward a highly progressive judicial activism, even acting as a positive legislator by creating new, regulatory legal norms. Several landmark judgments, such as Decision Number 90/PUU-XXI/2023 concerning the age limit for presidential and vice-presidential candidates, Decision Number 60/PUU-XXII/2024 concerning the nomination threshold for regional heads, and Decision Number 62/PUU-XXII/2024 concerning the presidential threshold, demonstrate the presence of judicial overreach, jurisprudential inconsistency, and infringement upon the boundaries of open legal policy (open legislative policy). The implications of this judicial activism include structural tensions with the legislature that trigger constitutional non-compliance, the threat of juristocracy or the shifting of mega-political issues to the courtroom. This article recommends the necessity of a simultaneous reconstruction at three levels: namely, the textual level through the formulation of guidelines on the limits of judgments; the institutional level through the strengthening of judicial ethics and an interpretation methodology based on proportionality; and the ecological level through the formalization of inter-institutional constitutional dialogue and the enactment of an independent Bill on the Procedural Law of the Constitutional Court with binding executorial deadlines.